Dakwah Berbasis Budaya Lokal pada Masyarakat Suku Lembak Kota Bengkulu - Ramdhani, Rahmat (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
The research aims to find out the description of Islamic religious rites conducted by the Lembak community. To understand and analyze the cultural propagation patterns of the Lembak people. the method used is qualitative with a symbolic interactionism approach. The research informants were six people from Dusun Besar Village and Panorama Village who were selected by purposive sampling. Data collection is done by observation, in-depth interviews, documentation studies, and literature studies. The results of the study show that: first, local culture-based propaganda in the Lembak tribe community which has been going on for a long time and has consistently maintained its sustainability is berayak, klop ngaji, and klop bedikir. Worthy is interpreted as a place of friendship for community members (mad'u) to learn about Islam with religious leaders/imams (da'i). While klop ngaji and klop bedikir as a medium for propagation gave birth to understanding and solemnness in carrying out Islamic teachings, namely fluent in reading and knowing the content of the Qur'an in the klop ngaji and living the contents of radat and Islamic poetry in the Book of Berzanji and the Book of Ulud in the klop bedikir. Routine activities carried out with practice produce synchronization and harmonization between Islamic da'wa and local culture. The three cultures have historical aspects that are synergistic with Islamic teachings, customary norms and social norms. While the content of da'wa in the culture is the internalization and dissemination of Islamic teachings so that it becomes energy and social capital in the lives of the Lembak people.